ANALYSIS OF HEMATOLOGICAL TERMS IN FRENCH AND UZBEK (Web of Teachers: Inderscience Research, 2025)
This study aims to analyze and compare hematological terms in French and Uzbek languages, exploring their linguistic structures, origins, and semantic nuances. Hematology, a branch of medicine concerning the study of blood and blood disorders, relies heavily on precise terminology for accurate communication among healthcare professionals. Given the linguistic diversity across different cultures, understanding the variations in medical terminology becomes crucial, especially in multilingual healthcare settings. This research employs comparative linguistic analysis to elucidate the similarities and differences between French and Uzbek hematological terms, shedding light on the cultural, historical, and linguistic influences shaping medical vocabulary in these languages.